The Impact of Noise on Agricultural Tractor Operator in Relation to Certain Operational Parameters: An Analytical Hierarchy Process (AHP) Approach - Željko Barač; Ivan Plaščak; Dorijan Radočaj; Mladen Jurišić (Agriculture)
This study examines the impact of noise inside the cabin of an agricultural tractor on the operator, focusing on operational parameters: agrotechnical surfaces, speed of movement, and tire pressure. Noise measurements were conducted on a LANDINI POWERFARM 100 tractor on agricultural fields and access roads. The tests followed HRN ISO 5008:2015 standards for smooth and rough tracks, and the noise was measured with a Metrel Multinorm device using an “A” filter, positioned according to HRN ISO 6396:2018 and ISO 5131:2018 standards. A two-factor analysis of variance was performed, considering tractor speed (“B”) and tire pressure (“C”). The Analytical Hierarchy Process (AHP) was applied to group the agronomic surfaces (“A”) into smooth and rough categories. By conducting a one-way ANOVA on the mean values of the dependent variables grouped by AHP, significant differences in noise were found. On the right side of the operator, significant noise differences were found between speeds B2, B3, and B4 (from 73.60 dB(A) to 73.99 dB(A)), with a decrease in noise as speed increased at C2. The coefficient of determination decreased from 78.99% to 44.93% with increasing speed. On the left side, significant differences in noise were found at tire pressure C1 at lower speeds, with increasing R2 values up to 50.89%, and similarly for C3 at higher speeds, reaching 72.61%.